PENGARUH MANAJEMEN LABA DAN KOMITE AUDIT TERHADAP CSR DENGAN MEDIASI KINERJA KEUANGAN - Anna Marina; Halimatus Sa’diyah; Amelia Fitri Nuraini (Jurnal Riset Akuntansi, 2025)
Financial reporting is essential for communicating financial performance to stakeholders. Profit, as a key financial indicator, is often affected by earnings management, which may pose information risks to investors. The audit committee plays a vital role in supervising financial reports and reducing earnings manipulation risks. Corporate social responsibility (CSR) is also influenced by financial performance and earnings management. This study examines the effects of earnings management and the audit committee on CSR, with financial performance as a mediating variable. Earnings management is measured using discretionary accruals, the audit committee by the number of members, financial performance by return on equity (ROE), and CSR by the CSRI index (GRI G4). Using quantitative methods, panel data from 33 conventional banks listed on the Indonesia Stock Exchange (IDX) for 2020–2022 (99 observations) were analyzed with SPSS 25. Results show earnings management negatively and insignificantly affects financial performance, while the audit committee has a positive but insignificant effect. Earnings management positively but insignificantly affects CSR, whereas the audit committee has a negative and significant effect. Financial performance does not mediate the earnings management–CSR relationship but does mediate the audit committee–CSR relationship. This study enhances understanding of financial reporting, audit oversight, and CSR implementation.